2008
DOI: 10.1159/000186049
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Bisabolol: Inhibitory Effects on Chemiluminescence of Human Neutrophil Bursts and Cell-Free Systems

Abstract: Human polymorphonuclear neutrophils (PMN), reactive oxygen species (ROS) and inflammatory reactions are closely interrelated, and increasing attention is being given to the search for new synthetic or natural antioxidant agents, capable of reducing ROS and consequent inflammation. It has been claimed that bisabolol (a monocyclic sesquiterpene alcohol) has an antioxidant/anti-inflammatory activity, but this has almost exclusively been investigated using chemical or biochemical tests. We studied the ability of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 52 publications
0
34
1
4
Order By: Relevance
“…Other findings in the literature suggest that (−)-α-bisabolol has marked anti-inflammatory action; however, these works used plants containing (−)-α-bisabolol (Moreno-Fernandes et al 1992;Braga et al 2009). There are no studies of the isolated drug in traditional models of inflammation and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Other findings in the literature suggest that (−)-α-bisabolol has marked anti-inflammatory action; however, these works used plants containing (−)-α-bisabolol (Moreno-Fernandes et al 1992;Braga et al 2009). There are no studies of the isolated drug in traditional models of inflammation and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that the sesquiterpene α-bisabolol (BISA) presents antitumor [6], peripheral nervous blocker [7], gastroprotective [8], leishimanicidal [9], antioxidant [10], mutagenic and antimutagenic [11], and wound healing [12] properties. There are also evidences showing that BISA reduced visceral nociceptive pain evoked by intracolonic administration of mustard oil (MO) as well as that induced by intraperitoneal injection of cyclophosphamide, possibly involving the inhibition of sensitization of primary afferent neuron terminals by prostaglandins [13].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effects of azulenes may be related to an influence on the pituitary and adrenal glands, through increased cortisone release and reduced histamine production (Rekka et al, 1996). In cell culture studies, both bisabolol and bisabolol oxide have been shown to inhibit 5-lipoxygenase activity (Braga et al, 2009). Apigenin 7- O -glucoside application has been shown to inhibit skin inflammation caused by application of xanthine-oxidase and cumene hydroperoxide in rats (Fuchs and Milbradt, 1993).…”
Section: Introductionmentioning
confidence: 99%